Analisis Efektivitas Sistem Pembayaran SPP Secara Manual di SMA Negeri 1 Maumere Tahun 2025 - Maria Gustiana Wanda; Maria Goreti Mao Tokan; Thresia Winarti (Universitas Nusa Nipa Maumere, 2025)
SMA Negeri 1 Maumere as one of the secondary education institutions continues to show development through improving the curriculum, infrastructure, and extracurricular programs. However, the tuition payment system that is still carried out manually poses various challenges in managing school financial administration. This study aims to analyze the effectiveness of the manual tuition payment system using the SWOT approach to identify the strengths, weaknesses, opportunities, and threats that affect the process. The results of the analysis show that although manual systems have been in use for a long time and are easy for financial officers to understand, they are still vulnerable to recording errors, process delays, and the risk of inaccurate data accumulation. In addition, the study found that the evaluation of this manual system makes an important contribution to the development of management science, especially in understanding the dynamics of administrative control and decision-making processes. The findings of the study recommend the development of a technology-based tuition payment system, such as online payments or integrated applications, as a solution to improve the efficiency, accuracy, and quality of administrative services at SMA Negeri 1 Maumere..